2017
DOI: 10.1002/2017gl072582
|View full text |Cite
|
Sign up to set email alerts
|

A new record of Atlantic sea surface salinity from 1896 to 2013 reveals the signatures of climate variability and long‐term trends

Abstract: Sea surface salinity (SSS) is a major ocean circulation component and indicator of the hydrological cycle. Here we investigate an unprecedented Atlantic SSS compilation from 1896 to 2013 and analyze the main modes of SSS decadal variability. Using principal component analysis, we find that the low‐latitude (tropical and subtropical) Atlantic and the subpolar Atlantic have distinct variability. Subpolar and low‐latitude SSS are negatively correlated, with subpolar anomalies leading low‐latitude anomalies by abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 83 publications
5
72
0
Order By: Relevance
“…Our findings rely on the model's representation of many complex and highly uncertain processes that may vary between models. We cannot test the historical forcing of the AMOC due to the lack of observations (Munoz et al, ; Srokosz et al, ), but the simulated (1920‐1980) AMOC variations are consistent with the CMIP5 multi‐model mean (Tandon & Kushner, ), and the simulations capture for example historical observations of sub‐polar sea surface salinity (Figure S15; Friedman et al, ) in addition to Atlantic and global SSTs.…”
Section: Summary Discussion and Conclusionmentioning
confidence: 94%
“…Our findings rely on the model's representation of many complex and highly uncertain processes that may vary between models. We cannot test the historical forcing of the AMOC due to the lack of observations (Munoz et al, ; Srokosz et al, ), but the simulated (1920‐1980) AMOC variations are consistent with the CMIP5 multi‐model mean (Tandon & Kushner, ), and the simulations capture for example historical observations of sub‐polar sea surface salinity (Figure S15; Friedman et al, ) in addition to Atlantic and global SSTs.…”
Section: Summary Discussion and Conclusionmentioning
confidence: 94%
“…Models predict that elevated global temperatures will cause increased precipitations and ice melt and thereby rapidly decrease salinity of polar and coastal waters of the North Atlantic region (Gibson & Najjar, 2000;Loder, van der Baaren, & Yashayaev, 2015). Increasing evaporation, on the other hand, is likely to result in elevated salinity in regions around the equator (Boyer, Levitus, Antonov, Locarnini, & Garcia, 2005;Friedman, Reverdin, Khodri, & Gastineau, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Atlantic Multidecadal Oscillation (AMO; Enfield et al, ; Schlesinger & Ramankutty, ) is reported to have played a role in the decadal changes in the STUW O 2 (Montes et al, ), which may be associated with decadal changes in the STUW production. Furthermore, the AMO is positively correlated with the decadal changes in the SSS within the North Atlantic subtropical gyre (Friedman et al, ). Thus, decadal changes in both indexes linked to the changes in the atmospheric forcings could indicate decadal changes in the STUW production.…”
Section: Discussionmentioning
confidence: 99%